Effectiveness analysis of accounting outsourcing transition - Lyakhovich, Galyna; Horodysky, Mykola; Hrabchuk, Irina; Vakun, Oksana (Public Policy and Accounting, 2020)
To ensure the best performance, businesses outsource individual business processes. However, implementing this step requires evaluating the effectiveness of such actions. The purpose of the article is to develop a techniques for analyzing the economic effectiveness of the transition to accounting outsourcing. To achieve the purpose, a critical evaluation of the approaches of scientists to determine the effectiveness of outsourcing has been made. Considering the identified disadvantages and advantages, as well as practical experience, the process of decision making on accounting outsourcing and evaluating its effectiveness is structured. The composition of the elements of the costs of maintaining accounting at the enterprise has been defined in the article. In order to evaluate the effectiveness of outsourcing the company it is suggested to use a technique that takes into account the indicators: timeliness of works and services under the terms of the outsourcing agreement; completeness of works and services under the terms of the outsourcing agreement. The technique was tested on five enterprises in different industries that planned to outsource accounting functions. It is established at what enterprises it is possible to achieve cost reduction and increase of effectiveness of resources use in the case of accounting outsourcing transition.